PRIMER DESIGN OF CVPDr DNA FRAGMENT SEQUENCES THAT AMPLIFY SPECIFIC FRAGMENTS TO DISTINCT THE RESISTANT FRAGMENT FROM Triphasia trifolia (Burm. F.) P. Wils. AND THE SUSCEPTIBLE FRAGMENT FROM Citrus nobilis Lour. - Ni Made Ayuratih Utami; I Gede Putu Wirawan; I Ketut Suada (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2020)
CVPDr is a DNA fragment that indicates that plants are resistant to CVPD. Previous research using primers that amplified 841 bp CVPDr fragment was able to amplify the fragment from Triphasia trifolia that considers being a resistant plant, Citrus aurantifolia var. seedless which considers being a tolerant plant, and some susceptible citrus plants to CVPD disease. In this study, we designed some primers that amplified only CVPDr DNA fragment from T. trifolia which consider as the resistant plant and a primer that amplified only DNA fragmen from Citrus nobilis which consider as the susceptible citrus plants. The primers for CVPDr on T. trifolia are TCATCTGCATGGGATACC for forward primer and GCCTTGAGCTTGTAAGTG for reverse primer which turned out to amplify the DNA of T. trifolia and also the C. nobilis cultivar Denpasar and only succeeded in not amplifying the C. nobilis cultivar Gianyar. The primers for CVPDr on C. nobilis are GAATGGCTTAGCAGAAAGG for forward primer and GGTTGTAGATGGACATAGG for reverse primer turned out can not only amplify the DNA C. nobilis but also amplify T. trifolia.